2021
DOI: 10.1080/00049530.2021.1981747
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia, rash impulsiveness, and reward sensitivity in relation to symptoms of exercise dependence in physically active young adults

Abstract: Objective. Exercise dependence refers to excessive exercise accompanied by addiction-like symptoms such as craving, tolerance, withdrawal, impaired control, and disruption of life domains. The present study investigated whether personality traits linked to substance and behavioral addictions show similar associations with symptoms of exercise dependence.Method. Alexithymia and two forms of impulsivity, rash impulsiveness and reward sensitivity, were assessed in relation to exercise dependence symptoms in a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 80 publications
3
10
1
Order By: Relevance
“…The present study yielded some findings that were expected and some that were unexpected. The SPSRQ-SR index of reward sensitivity showed a positive relationship with exercise dependence symptoms in both non-binge and severe binge eater groups alike, consistent with previous work that did not distinguish between primary and secondary exercise dependence (Lyvers et al, 2021), and presumably reflecting the rewarding psychological and health benefits of exercise (Back et al, 2019;Dietrich, 2006;Freimuth et al, 2011;WHO, 2010). By contrast, the SPSRQ-SP index of punishment sensitivity was negatively related to exercise dependence symptoms in both groups.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The present study yielded some findings that were expected and some that were unexpected. The SPSRQ-SR index of reward sensitivity showed a positive relationship with exercise dependence symptoms in both non-binge and severe binge eater groups alike, consistent with previous work that did not distinguish between primary and secondary exercise dependence (Lyvers et al, 2021), and presumably reflecting the rewarding psychological and health benefits of exercise (Back et al, 2019;Dietrich, 2006;Freimuth et al, 2011;WHO, 2010). By contrast, the SPSRQ-SP index of punishment sensitivity was negatively related to exercise dependence symptoms in both groups.…”
Section: Discussionsupporting
confidence: 86%
“…This result could conceivably be explained by an aversion to extreme exertion or risk of pain in those who scored high on SP, which has been associated with high neuroticism (Lee-Winn et al, 2016) and high alexithymia (Lyvers et al, 2012) in previous work; the positive association of SP with alexithymia was replicated in the present study. Alexithymia as measured by the TAS-20, which was reported to show a positive association with exercise dependence symptoms in previous work (Lyvers et al, 2021), only showed such an association in non-binge eaters in the present study, presumably reflecting a role of alexithymia in primary but not secondary exercise dependence. In severe binge eaters, alexithymia was unrelated to exercise dependence symptoms, which might be explained by the high SP observed in the severe binge eater group (their mean SPSRQ-SP score was nearly double that in the non-binge eater group) given the negative association of SP with exercise dependence symptoms and the positive association of alexithymia with SP.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations